Critical Thinking for Quality Education - Mainali, Bhawani Prasad (Academic Voices: A Multidisciplinary Journal, 2011)
Critical thinking is a recent educational paradigm. It is a powerful thinking skill that empowers learners and facilitates creative and qualitative teaching/learning process. This article deals with the concept of critical thinking for quality education. Moreover, it also identifies the rationale of critical thinking and its implications in Nepalese education . Keywords Critical thinking, creativity, concretization, culture of silence, quality education. DOI: http://dx.doi.org/10.3126/av.v1i0.5300 Academic Voices 2011; 1: 6-12